English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

the answer in radical form?

2007-05-28 15:34:38 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

sqrt((-8-(-3))^2 + (-3 - 6)^2)
sqrt(-5^2 + -9^2)
sqrt(106)

I'm not sure why people give such poor answers. It certainly isn't remotely funny.

2007-05-28 15:38:07 · answer #1 · answered by Anonymous · 1 0

8 and 5

2007-05-28 15:36:26 · answer #2 · answered by tinkerbellluvr3668 1 · 0 2

Use the distance formula. sqrt((-1 - 3)^2 + (-3-(-6))^2) = sqrt((-4)^2+(3)^2) = sqrt(16+9) =sqrt(25) = 5. Sqrt stands for square root.

2016-05-20 03:15:15 · answer #3 · answered by ? 3 · 0 0

d² = (- 3 - 6)² + (- 8 + 3)²
d² = 81 + 25
d² = 106
d = √106

2007-05-28 21:50:22 · answer #4 · answered by Como 7 · 0 0

distance = √((x1-x2)²+(y1-y2)²)
=√((6-(-3)²)+((-3)-(-8)²))
=√(9²+5²) =√(81+25) =√106

2007-05-28 15:39:23 · answer #5 · answered by Chris S 5 · 0 0

five miles, give or take a few feet.

2007-05-28 15:37:13 · answer #6 · answered by Bob Thompson 7 · 0 2

fedest.com, questions and answers